Espaço poroso avaliado por tomografia e propriedades hídricas e mecânicas em solos argilosos sob culturas anuais e campo natural - Scheid, Douglas Leandro (2020)
The growing demand for food and energy causes an intensification in agriculture, which uses larger machines and results in high pressures applied to the soil. As the pressures increases there are changes in the soil porous system, affecting the permeability of the porous system. The general objective was to understand the mechanical behavior of the soil and the effect of normal and transient pressures and the corresponding permeability of different classes of soil in the Plateau of Rio Grande do Sul, making use of mechanical tests, evaluating permeability and employing X-ray scanning. Soil samples were collected in profiles under native grassland and agricultural use, in two soil types: “Latossolo Vermelho” and “Nitossolo Vermelho” (Brazilian Soil Classification System), both are Typic Hapludox by Soil Taxonomy. Samples were collected with volumetric cylinders in the central part of each horizon (Hz). In the samples, the water retention curve, soil permeability to air (Ka), hydraulic conductivity of saturated soil (Ksat), pre-consolidation pressure and compression index were measured. Compressibility tests were performed on two sets of samples: (i) application of pressures of 12.5, 25, 50, 100, 200, 400 and 800 kPa sequentially, with pressure application time for 20 minutes and (ii) application of pressures 12.5, 25, 50, 100, 200, 400 and 800 kPa with 30 loading and unloading cycles of each pressure. The test was interrupted after applying each pressure to measure the Ka. Also, X-ray computed tomography images were analyzed to characterize the macroposity. The saturated hydraulic conductivity of the soil showed that the soil structure changed, with a three to fivefold reduction in agricultural cultivation to the native grassland. The pre-compression stress was higher in the soils under the native grassland and the compression index was higher in the surface horizon of the soil, that the showed surface layers of the soil are susceptible to the compaction and the subsurface already damaged due to the propagation of the pressures applied by traffic of machines. The analysis of tomography images allowed to distinguish the structural condition of the soils under different uses. In soils under native grasssland, the pore network is more connected, with higher connectivity values and larger pores. In soils under agricultural cultivation, the surface horizon has a predominance of smaller pores and less connectivity. However, the permeability of the soil was sensitive to the rearrangement of the soil structure due to the application of pressures, as already a comparative low pressure of 12,5 kPa changed de Ka. The air permeability of soil was not altered due to the type of static or dynamic compression test. X-ray computed tomography technique is useful in detecting changes in the soil structure, allowing the exploration of the behavior of the intensity properties such as saturated hydraulic conductivity and the permeability of the soil to air.